From Embodied Shame to Intimacy: How Cultural Scripts Shape Recovery Among Israeli Men After Childhood Sexual Abuse. - Nimni, Amos; Gueta, Keren (Psychology of Men & Masculinities, 2026)
Men's recovery from childhood sexual abuse unfolds within cultural scripts of masculinity that shape bodies, emotions, and relationships. Qualitative narrative inquiry with 25 Israeli men (Secular Jewish, Ultra-Orthodox Jewish, and Arab). Semistructured interviews were thematically analyzed. Four recurring, nonlinear themes describe postchildhood sexual abuse adaptation: (a) body image and self-worth (shame, hypersurveillance, and feeling "not man enough"); (b) embodied dissociation and numbness (disconnection from sensation and presence); (c) safety and control (hypervigilance, ritualized control, religious discipline, risk); and (d) intimacy and relationships (avoidance, disclosure burdens, ambivalence between sex and closeness). Across groups, different cultural anchors (Sabra toughness; Ultra-Orthodox modesty and discipline; Arab family honor) constrained vulnerability and help-seeking in similar ways. Findings extend trauma models by foregrounding culturally situated embodiments and showing how masculine norms shape recovery pathways. Public Significance Statement: This study underscored the role of cultural scripts of masculinity in men's coping with childhood sexual abuse and the importance of culturally responsive support that recognizes embodied impacts, disclosure barriers, and nonlinear recovery.